Colovesical fistula as a complication of colonic diverticulosis: diagnosis with virtual colonoscopy - Işılay NADİR; Yasemin ÖZİN; Zeki Mesut Yalın KILIÇ; Dilek OĞUZ; Aysel ÜLKER; Kemal ARDA (Turkish Journal of Gastroenterology, 2019)
-